Palm oil thorn induced tumour like lesion: a review of 3 cases - Che Ahmad, Aminudin; Zakaria@Mohamad, Zamzuri; Zulkifly, Ahmad Hafiz; Ab Rahman, Jamalludin (2006)
It is not widely recognized that palm oil thorn injuries can produce progressive and persistent reaction in the bone, joint and surrounding soft tissue. The natural history is unique and most of the investigation is inconclusive. We review three cases of tumour like lesion: two were around the elbows and one at the foot, which developed following injuries by palm oil thorn. The typical clinical presentation is transient acute synovial followed by a relative asymptomatic period and later by chronic or recurrent inflammation mimicking septic arthritis, osteomyelitis or bone tumour often after the thorn injury was forgotten. Hand is the most commonly affected. Lesion of the elbows and foot are very rare. The tissue for culture and histopathological examination, and administration of broad spectrum antibiotics are needed for the treatment although they are negative and inconclusive. The definite treatment includes operative debridement and removal of thorn particles, eventhough most cases the particles cannot be found either due to irrigation or too small to be seen. In conclusion, high index of suspicious is needed to include palm oil thorn injuries as a differential diagnosis of granulomatous lesion of bones and joints.